Severity related neuroanatomical and spontaneous functional activity alteration in adolescents with major depressive disorder - Zhang, Xiaoliu; Cao, Jun; Huang, Qian; Hong, Su; Dai, Linqi; Chen, Xiaorong; Chen, Jianmei; Ai, Ming; Gan, Yao; He, Jinglan; Kuang, Li (Frontiers in Psychiatry, 2023)
Major depressive disorder (MDD) is a disabling and severe psychiatric disorder with a high rate of prevalence, and adolescence is one of the most probable period for the first onset. The neurobiological mechanism underlying the adolescent MDD remains explored. In this study, we examined the cortical and subcortical alterations of neuroanatomical structures and spontaneous functional activation in fifty unmedicated adolescents with MDD versus thirty-nine healthy controls through the combined structural and resting-state functional magnetic resonance imaging. Significantly altered regional gray matter volume was found at broader fronto-temporal-parietal and subcortical brain areas involved with various forms of information processing in adolescent MDD. Specifically, the increased GM volume at left paracentral lobule and right supplementary motor cortex were significantly correlated with the depression severity in adolescent MDD. Further, lower cortical thickness at brain areas responsible for visual and auditory processing as well as motor movements were found in adolescent MDD. The lower cortical thickness at superior premotor subdivision was positively correlated with the course of disease. Moreover, higher spontaneous neuronal activity was found at anterior cingulum and medial prefrontal cortex, and this hyperactivity was also negatively correlated with the course of disease. It potentially reflected the rumination, impaired concentration and physiological arousal in adolescent MDD. The abnormal structural and functional findings at corticosubcortical areas implied the dysfunctional cognitive control and emotional regulations in adolescent depression. The findings might help elaborate the underlying neural mechanisms of MDD in adolescents.